Semantic Roles in Emma Watson’s Speech on Gender Equality at He for She Campaign - Vanny Annisa Putri Hendarto; Heri Heryono (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This research intends to investigate and analyze the semantic roles used in Emma Watson's speech, as well as their significance. The study was conducted using a descripttive qualitative research methodology. The information was derived from Emma Watson's speech at the HeForShe script at the United Nations. From the studies there are only found six types of semantic roles which are agent (39%), experiencer (16%), goal (7%), source (16%), theme (20%), and location (2%). In addition to identifying the semantic role, the researcher also identified the meaning contained in the speech. Kinds of meaning that we can found in this research are only four types, there are conceptual meaning (86%), connotative meaning (6%), affective meaning (6%), and reflected meaning (2%). The types of semantic roles were analyzed by identifying each sentence.